Efficacy of the power centering for seniors intervention on physical functional performance in older community-dwelling adults: a secondary analysis of a randomised controlled trial - Roland Rössler; Mathias Birrer; Aaron Haslbauer; Jay Goldfarb; Anton De Spiegeleer; Irene Härdi; Reto W. Kressig (Scientific Reports)
Abstract Maintaining physical function and mobility is essential for older adults to preserve independence, reduce fall risk, and minimise dependence on care. “Power Centering for Seniors” (PCS) is a mindfulness-based, proprioceptive training programme combining Tai Chi and Qi Gong with functional strength and balance practices. This study assessed the efficacy of the PCS programme on physical functional performance in older community-dwelling adults. The study included 57 participants aged 70 years or older, randomised into an intervention group (IG) or a control group (CG). The PCS intervention consisted of 24 supervised sessions over 12 weeks, with additional home exercises. Physical functional performance was measured using the Continuous Scale Physical Functional Performance 10 (CS-PFP-10) test, focusing on the subdomain Lower Body Strength and Balance & Coordination. A linear mixed-effects model was used to analyse the data, adjusting for baseline CS-PFP-10 scores, sex, and age. Fifty-one participants completed the study. The PCS intervention led to non-significant improvements in the CS-PFP-10 total score compared to the CG, with an adjusted difference of 2.05 points (95% CI: −0.78 to 4.89; p = 0.163; Cohen’s d = 0.403). Similar trends were observed in the sub-scores for Lower Body Strength (adjusted difference: 2.84, 95% CI: −0.21 to 5.90; p = 0.074; Cohen’s d = 0.517) and Balance & Coordination (adjusted difference: 3.34, 95% CI: −0.09 to 6.79; p = 0.063; Cohen’s d = 0.541). The PCS intervention showed potential for improving physical function in older adults in areas critical for maintaining mobility and independence. While trends were favourable, the results did not reach statistical significance. Trial registration ClinicalTrials.gov NCT04861831; date of registration: April 27, 2021.